To simplify this expression, we must combine like terms. This means that we have to add or subtract the coefficients of the same variables, meaning we can only add variable a's together and variable b's together, they must stay separate.
3a + 2b - 8a + b
The first thing that we should do is to rearrange this expression so that the terms with the same variables are next to one another.
3a - 8a + 2b + b
Next, we can combine these terms by adding/subtracting their coefficients.
-5a + 3b
We can also write this as:
3b - 5a
Therefore, your answer is 3b - 5a.
Hope this helps!
To simplify 3a + 2b - 8a + b, we need to combine like terms. Like terms are terms that share common variables. In this expression, the two variables are terms with a and terms with b. The terms that have a are 3a and -8a. The terms that have b are 2b and b. Now we can separate them and simplify.
(3a - 8a) + (2b + b)
-5a + 3b
The positive difference between the square of the sum of the first five positive integers and the sum of the first five positive perfect squares is 170. This is obtained by taking the sum of first five numbers, squaring the sum and subtracting the sum of first five perfect squares.
The sum of first five positive integers = 1+2+3+4+5 = 15
Square of the sum of the first five positive integers = 15² = 225
The sum of the first five positive perfect squares =1²+2²+3²+4²+5²
=1+4+9+16+25
=55
The positive differenece = 225-55=170
Hence the positive difference between the square of the sum of the first five positive integers and the sum of the first five positive perfect squares is 170.
Learn more about arithmetic sequence here:
#SPJ2
Answer:
Step-by-step explanation:
The square of the sum of the first five positive integers:
(1 + 2 + 3 + 4 + 5)² = 15² = 225
The sum of the first positive perfect square:
1² + 2² + 3² + 4² + 5² = 1 + 4 + 9 + 16 + 25 = 55
225 - 55 = 200